From the Sublime to the Cosmic. Walter Benjamin’s Planetarium - Giannuzzi, Mariaenrica (Aisthesis, 2025)
This contribution surveys the presence of Walter Benjamin’s philosophy in the environmental humanities. As I argue, Benjamin’s philosophy emerged in the debate on the temporality of climate change and instantiated a cosmic predicament. To clarify the meaning of the cosmic predicament, first, I reconstruct the terms of the debate; second, I analyze Benjamin’s aphorism To the Planetarium that concludes the experimental prose collection One-Way Street (1928). By reading the aphorism closely, I emphasize Benjamin’s quite explicit critique of Kantian modernity, which is defined as domination over nature, as Benjamin’s text posits. Through the scientific formulation of natural laws, morality, and the feeling of the sublime, according to Benjamin, modernity has relinquished a performative approach to nature, which, in turn, can reconfigure nature as an experience of cosmic trance (Rausch).